2020
DOI: 10.1177/1071100720917645
|View full text |Cite
|
Sign up to set email alerts
|

Necessity of Interfragmentary Lag Screws in Precontoured Lateral Locking Plate Fixation for Supination-External Rotation Lateral Malleolar Fractures

Abstract: Background: Interfragmentary lag screws, protected by a plate, have been applied for many years in the treatment of supination-external rotation (SER) ankle fractures. Recently, similar biomechanical stability was found between fixation completed with a plate and lag screw and a plate alone. The aim of this study was to determine whether interfragmentary lag screws are necessary during precontoured lateral locking plate fixation for SER lateral malleolar fractures. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…In our study, we did not use interfragmentary lag screws. A recent prospective randomized study demonstrated that interfragmentary lag screws are not essential for precontoured lateral LP fixation in non‐comminuted supination‐external rotation lateral malleolar fractures, provided that intraoperative compression with a reduction clamp is performed 40 . The lag screw head and purchase impede proper plate placement.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not use interfragmentary lag screws. A recent prospective randomized study demonstrated that interfragmentary lag screws are not essential for precontoured lateral LP fixation in non‐comminuted supination‐external rotation lateral malleolar fractures, provided that intraoperative compression with a reduction clamp is performed 40 . The lag screw head and purchase impede proper plate placement.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the proximal portion of the two-dimensionally pre-contoured plate may not contact properly with the fibular body if it is adjusted to the lateral malleolus, which interrupts the proper placement of the proximal screws. In addition, a twodimensionally pre-contoured plate may result in impingement between the plate and the bulky head of the lag screw inserted in advance [7].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of surgical fixation devices for an isolated Weber B type fracture, lag screws in combination with locking plates are preferred currently [6]. With the development of a pre-contoured locking plate, however, studies showed that plate itself can provide sufficient fixation power beyond its role of neutralizing the fixation accomplished by lag screws [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a measure of radiographic outcome, the Kellgren and Lawrence (K&L) grading scale was used to assess arthritic changes after ankle fractures. 11,23 In addition, the quality of fracture reduction was evaluated using previously defined criteria: acceptable reduction was defined as <2 mm of displacement of any fracture line near the joint or 2 mm of translation of the talus relative to its normal articulation with the tibial plafond. 17,33 The K&L grade and quality of fracture reduction were determined independently by 2 orthopedic surgeons (Y.H.P., H.W.C.)…”
Section: Methodsmentioning
confidence: 99%